O papel docente na alfabetização e leitura com crianças no início da escolarização: a perspectiva de artigos científicos publicados entre 2016 e 2020 - Carvalho, Joseleine (Universidade Federal de São Carlos, 2021)
This course conclusion work focuses on the teaching role in the initial literacy of children in the perspective of the publications of scientific articles in the last five years. Its general objective was to understand the teaching role in the initial literacy of children in Brazilian schools, considering the indications offered by scientific articles published in the SciELO digital database, from 2016 to 2020. It started from the understanding that the concepts of learning moved from a more individualistic theoretical focus to a more community focus. The study had a theoretical character and relied on the methodological procedures of bibliographic research and the sources used were collected in the SciELO digital database. The main results obtained indicated that, in the Brazilian scenario, literacy has been guided by the National Pact for Literacy in the Right Age and the publications have almost entirely focused on the constructivist conception of learning. The conclusions of this work suggest that little has been published about the dialogic conception in the context of children's literacy in the initial period of schooling in Brazil, but successful actions have been developed and scientifically proven in other countries, so there is a need for publications that prove the that teachers and school managers have demonstrated in spaces of continuing education and spaces for dialogue and exchange of experiences.
The teaching role in literacy and reading with children at the beginning of schooling: the perspective of scientific articles published between 2016 and 2020
El papel docente en alfabetización y lectura con niños al inicio de la escolaridad: la perspectiva de los artículos científicos publicados entre 2016 y 2020
Keywords: Alfabetização; Formação de professores; Leitura dialógica; Educação Básica; Literacy; Teacher education; Dialogical reading; Basic education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO